Identity Crisis: Cosplay as Cultural Hybridization. - Casey, Daniel M. (Tufts Archival Research Center, 2005)
This paper examines the phenomenon of "cosplay" in America and attempts to determine whether it is a twenty-first century form of Orientalism or the result of cultural hybdridization. Cosplay, short for "costume play," is a subculture of Japanese anime (animation) and manga (comics) fandom in which fans dress up as their favorite characters. In an era of increasingly globalized media, cosplay is a uniquely Japanese form of soft power which, playing upon the "identificatory fantasy," enables Western participants to assume identities and achieve levels of Otherness in ways which Western cultural products cannot equal. The average cosplayer is not merely putting on a costume; the experience is one of metamorphosis, a transformation of identity, a phenomenon which I explore on both an individual and societal level. Yet, all of this begs the question of intent: why do people do it? Is this simply a form of subcultural escapism or is it yet another Orientalist mode, a vehicle for Western fetishization and domination of Eastern identities? There is a rich historical tradition of Western cultural imperialism in regards to Japanese culture, beginning with popularization of Japanese ukiyo-e prints in Paris in the seventeenth century, expanding from there. This is by no means a new behavior, but it is a relatively unexamined one and through the paper, I examine the the role of fandom in the formation of modern identity, trace the historical roots of cosplay, and finally I seek to synthesize scholarship with fieldwork in order to determine whether cosplay is a manifestation of cultural imperialism of cultural hybridity.